2010
DOI: 10.1111/j.1600-0714.2010.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the expression of cdk4 and cdk6 proteins in oral cancer and premalignant lesions

Abstract: Overexpressions of cdk4 and cdk6 were observed in OSCC, indicating that these two proteins play a crucial role in OSCC. The aberrant expression of cdk4 was found in OL with dysplasia, suggesting that cdk4 may be involved in the early event of carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…CDK5 has been shown to be involved in lung cancer (Choi et al 2009;Liu et al 2010). The expression of CDK 6 is also altered in oral cancer (Poomsawat et al 2010). CDK7 polymorphisms have been shown to have an eVect on breast cancer (Jeon et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK5 has been shown to be involved in lung cancer (Choi et al 2009;Liu et al 2010). The expression of CDK 6 is also altered in oral cancer (Poomsawat et al 2010). CDK7 polymorphisms have been shown to have an eVect on breast cancer (Jeon et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…CDK2 expression or activity has been used for the prognosis of breast (Kim et al 2008), ovarian (Marone et al 1998) and oral (Mihara et al 2001) cancers. Aberrant expression of CDK4 has been implicated in ovarian (Kusume et al 1999), urinary bladder , endometrial (Semczuk et al 2004) and oral (Poomsawat et al 2010) cancers. CDK5 has been shown to be involved in lung cancer (Choi et al 2009;Liu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have been reported on expression of CDKs in human malignancies indicating its oncogenic property. [121617]…”
Section: Discussionmentioning
confidence: 99%
“…in their study on endometrial carcinomas who concluded it as having a different “functional status” or a “resting status” of CDK4. [12]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation